Evolution of a giant debris flow in the transitional mountainous region between the Tibetan Plateau and the Qinling Mountain range, Western China: Constraints from broadband seismic records. (15th October 2017) - Huang, Xinghui; Li, Zhengyuan; Yu, Dan; Xu, Qiang; Fan, Junyi; Hao, Zhen; Niu, Yanping
Graphical abstract: Highlights: Broadband seismic stations can detect a debris flow several minutes in advance. Seismic signals before and after a debris flow formation are distinctively different. The formation time of the Sanyanyu debris flow is 23:33:15 (Beijing time, UTC + 8). The Sanyanyu debris flow has five stages with different discharge characteristics. Abstract: The catastrophic Sanyanyu and Luojiayu debris flows, which were induced by heavy rainfall, occurred at approximately midnight, August 7th, 2010 (Beijing time, UTC + 8) and claimed 1, 765 lives. Most seismic stations located within 150 km did not detect the debris flows except for the closest seismic station, ZHQ, indicating that the seismic signals generated by the debris flows decayed rapidly. We analyzed broadband seismic signals from the ZHQ seismic station, beginning approximately 20 min before the outbreak of the Sanyanyu debris flow, to rebuild its evolution processes. Seismic signals can detect development of the Sanyanyu debris flow approximately 20 min after a heavy rain started falling in its initiation area; this time was characterized by a gradual increase in seismic amplitude accompanied by a series of spike signals that were probably generated by rock collapses within the catchment. The frequency contents and the characteristics of seismic signals before and after 23:33:15 (T1 ) are distinctively different, which we interpret as being generated by a large quantity of flowing material entering the main channel, marking the formation of the Sanyanyu debris flow. We attribute seismic amplitude increases between 23:33:15 (T1 ) and 23:34:26 (T2 ) and between 23:35:40 (T3 ) and 23:36:49 (T4 ) to entrainment of the deposit material after initiation of the debris flow and to its flow through a colluvial deposit area, respectively. The main frequency band broadening of seismic signals after 23:37:30 (T5 ) is believed to have been induced by impacts between the flowing material and check dams.